The G Protein-Coupled Receptors Handbook - Devi, Lakshmi A.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
G protein-coupled receptors (GPCRs) are involved in many processes in the human body relevant to health and disease, and consequently are the targets of approximately 70% of pharmacological therapeutics and a major source of new drug candidates. In The G Protein-Coupled Receptors Handbook, leading academic researchers comprehensively survey the many recent advances that have occurred in the GPCR field. The authors describe the current knowledge of GPCR receptor structure and function, the different mechanisms involved in the regulation of GPCR function, and the role of pharmacological chaperones in GPCR folding and maturation. They present new findings about how GPCR dimerization/oligomerization modifies the properties of individual receptors, and show how recent developments are leading to significant advances in drug discovery. They also discuss the most recent developments that could lead to new discoveries: the role of GPCRs in mediating pain, the development of receptor-type selective drugs based on the structural plasticity of receptor activation, and the identification of natural ligands of orphan GPCRs (deorphanization) as possible drug targets. Authoritative and cutting-edge, The G Protein-Coupled Receptors Handbook offers pharmacologists, biochemists, and neuroscientists an exhaustive review of the progress made in understanding how GPCRs are activated and regulated, key factors in exploiting GPCRs for drug development.
GPCRs: Structure and Function -- Structure$1 (BFunction Relationships in G Protein-Coupled Receptors -- Molecular Mechanisms Involved in the Activation of Rhodopsin-Like Seven-Transmembrane Receptors -- GPCR Folding and Maturation -- Regulated Membrane Trafficking and Proteolysis of GPCRs -- GPCR Activity and Its Regulators -- Heterotrimeric G Proteins and Their Effector Pathways -- RGS Proteins -- G Protein-Coupled Receptor Kinases -- Regulators of GPCR Activity -- GPCR Interacting Proteins -- GPCR Dimerization/Oligomerization -- Biophysical and Biochemical Methods to Study GPCR Oligomerization -- Oligomerization Domains of G Protein-Coupled Receptors -- Functional Complementation and the Analysis of GPCR Dimerization -- The Role of Oligomerization in G Protein-Coupled Receptor Maturation -- Receptor Oligomerization and Trafficking -- Modulation of Receptor Pharmacology by G Protein-Coupled Receptor Dimerization -- Recent Developments in Drug Discovery -- Role of Heteromeric GPCR Interactions in Pain/Analgesia -- Conformational Plasticity of GPCR Binding Sites -- De-Orphanizing GPCRs and Drug Development.s
Keywords: Medicine; Neurosciences; Biomedicine; Neurosciences; Electronic books